Investigation of landslide areas in Tokat-Almus road between Bakımlı-Almus by the PS-InSAR method (Türkiye) - Oktar Osman (Open Geosciences)
Landslides and ground deformations pose significant risks to infrastructure safety, leading to road damage, economic losses, and potential hazards for transportation networks. There are visible deformations in the section of the Tokat-Almus road between the village of Bakımlı and the town of Almus. In this part of the road, the road has narrowed due to landslides, and subsidence has occurred in some sections. To analyze and quantify these deformations, the persistent scatterer interferometric synthetic aperture radar (PS-InSAR) method was applied. Both ascending and descending synthetic aperture radar (SAR) images covering the same period (30 images between February 2022 and February 2023) were analyzed. Thus, the annual movements in the line of sight (LOS) were obtained. Considering the annual velocities in the LOS direction and given the PS-InSAR analysis results, the highest annual subsidence value was found to be 22.9 mm and the highest annual uplift value to be 17.2 mm. Standard deviation values for these velocities were determined to range between 0.7 and 10.5 mm. Decomposition was carried out to examine LOS results in detail. Examining the annual velocities in the vertical direction, the highest annual subsidence value was found to be 37 mm and the highest annual uplift value to be 23 mm. Considering the annual velocities in the horizontal direction, the annual velocity rate was found to range between −19 and 24 mm. The surface movements determined in this study provide significant contributions to the planning of engineering measures, especially in landslide risk areas such as the Tokat-Almus road. The results of the study provide valuable inferences in terms of road safety and disaster management by demonstrating the effectiveness of the PS-InSAR method in long-term deformation monitoring processes. The obtained data can be guiding not only for the improvement of highway routes and taking structural measures in landslide risk areas, but also for the development of disaster management strategies.